From theory to practice: improving the impact of health services research - Brazil, Kevin (BioMed Central, 2005)
BACKGROUND: While significant strides have been made in health research, the incorporation of research evidence into healthcare decision-making has been marginal. The purpose of this paper is to provide an overview of how the utility of health services research can be improved through the use of theory. Integrating theory into health services research can improve research methodology and encourage stronger collaboration with decision-makers. DISCUSSION: Recognizing the importance of theory calls for new expectations in the practice of health services research. These include: the formation of interdisciplinary research teams; broadening the training for those who will practice health services research; and supportive organizational conditions that promote collaboration between researchers and decision makers. Further, funding bodies can provide a significant role in guiding and supporting the use of theory in the practice of health services research. SUMMARY: Institutions and researchers should incorporate the use of theory if health services research is to fulfill its potential for improving the delivery of health care.